Espacios y prácticas rituales en Cerro Lampay (2400-2200 a.C.) - Centeno Sara-Lafosse, Rafael (2007)
Current data from the site of Cerro Lampay (an architectural compound of the Late Archaic Period) provide new insights on the architectural design that characterizes the early complex societies of the north central coast. Excavations at this site have provided a detailed record of the major traits that can be found in a typical architectural compound that correspond to the Late Archaic Period in this region. The analysis of the spatial structure and the sensorial experience of the architecture of Cerro Lampay suggest a scenario of a human community in which leaderships were emerging whereas dual principles of social organization were also appearing. The results of these analyses are compared with recent finds on other neighboring sites such as Caral, in order to propose new perspectives to understand the rise of social complexity in the Central Andes.